The future of HRM in a world of persistent virtual reality - Kumar, Dinesh; Suthar, Nidhi; Taherdoost, Hamed; Madanchian, Mitra (Emerald Publishing Limited, 2025)
As virtual reality (VR) technology not only redefines the boundaries of human resource management (HRM) but also offers innovative solutions to long-standing challenges in the field, a comprehensive understanding of the transformative impact of VR on HRM is critical now more than ever. The Future of HRM in a World of Persistent Virtual Reality delves into how the integration of VR technologies is revolutionizing HRM practices, challenging traditional norms, and creating new paradigms for work, employee engagement, training, and recruitment. A timely and essential exploration into the rapidly evolving field of HRM in the context of persistent VR, the chapters within provide insights into current applications and future potential. Treading new ground by synthesizing interdisciplinary perspectives, including social sciences, technology, psychology, and business studies, offering a holistic view of the subject, The Future of HRM in a World of Persistent Virtual Reality addresses the gap in existing literature by focusing on the practical, ethical, and theoretical implications of VR in HRM, which have not been extensively explored to date.
Includes index.
Keywords: Personnel management -- Technological innovations.; Virtual reality.; Business & Economics -- Human Resources & Personnel Management.; Personnel and human resources management.; elektronické knihy; electronic books